A Diis Electa: a Chapter in the Religious History of the Third Century - Nock, Arthur Darby (Harvard theological review, 1930)
The excavation of a site commonly gives us a neat and definite stratification of successive periods. Although the religious history of the Empire is less fortunate, nevertheless it has turning points and we can remark certain features as characteristic of particular periods. It is not that the phenomena in question are confined to these periods, but that they appear in them with special emphasis. The purpose of this paper is to consider a group of inscriptions which throw some light on the religious atmosphere of Rome in the middle of the third century of our era.